Viscoelastic property and cell adhesion process of cultured fibroblasts on different self-assembled monolayers monitored by acoustic wave biosensor - Y. Viturawong (2018)
© Springer International Publishing Switzerland 2014. A quartz crystal microbalance (QCM) technique was used to reveal the effect of alkanethiol self-assembled monolayers (SAMs) on the viscoelastic property and cell adhesion process of cultured fibroblasts (L929), by measuring the change in frequency (∆f) and resistance (∆R). Four types of SAMs having different functional groups including hydroxyl (OH), carboxylic acid (COOH), amine (NH2) and methyl (CH3) were used in this study. The QCM measurements during cell adhesion showed that floating cells were rapidly adsorbed on all functionalized surfaces as a soft cell monolayer which their stiffness was increased by cell spreading process. Initially, the ∆f and ∆R were both positive shifts for COOH, OH and NH2 surfaces indicated fluid-like behavior of adherent cells. A multi-step decreasing of both ∆f and ∆R were observed in case of COOH and OH surfaces represented solid-like behavior of cell spreading. The CH3 surface was used as a control because no cell adhesion occurs. QCM responses and morphological changes during cell adhesion process were resulted from viscoelastic nature of mammalian cells. The changes of cell morphology and viscoelastic property during cell adhesion process strongly depend on the surface functionality which can be observed by QCM technique.